Keterampilan Kerja Perempuan Penenun Sutra Mandar Dalam Menopang Ekonomi Keluarga (Studi Kasus Desa Pambusuang, Kec. Balanipa, Kab. Polman) - Y, Mawadda; Ashdaq, Muhammad; Qamariah, Nur; Fauzan, Muhammad (Jurnal Manarang Manajemen dan Bisnis, 2022)
This study aims to determine the work skills of women Mandar silk weavers in supporting the family economy (Case study in Pambusuang Village, Balanipa District, Kab, Polman The research approach used in this study is an ethnographic qualitative research method, because this research is related to a culture, namely the competence of women in weaving Mandar silk sarongs, in this study describing an event according to reality. The location of the research was carried out in Pambusuang Village, Balanipa District, Polewali Mandar Regency, which was on Poro Polewali Majene Street. The informants used in this study were 10 women weavers of Mandar silk sarongs. The data analysis used in this research is descriptive data analysis method. Qualitative descriptive analysis method is data analysis that produces written or spoken words from people and behaviors that can be observed by individuals holistically (whole). The results showed that the work competencies of the women in Pambusuang Village in weaving Mandar silk they already had, namely they already knew how to make quality silk fabrics, namely by 1) Using good and clean weaving equipment, 2) using quality yarn raw materials, 3) a stable sitting position during the weaving process, 4) maintain cleanliness while tightening the thread so that it is neat, 5) be patient in weaving. The income of the women silk weavers from the sale of silk cloth is uncertain because it depends on the amount sold. In general, their income from the sale of Mandar silk cloth ranges from Rp. 200,000 – Rp. 800,000/month. This income has not been able to cover their family's daily needs because some of the money they use to buy back the raw materials needed for weaving Mandar silk.